Alpha blockers in the management of ureteric lithiasis: A meta‐analysis. Issue 1 (January 2017) - Raison, Nicholas; Ahmed, Kamran; Brunckhorst, Oliver; Dasgupta, Prokar
Summary: Introduction: Effective medical expulsion for ureteric stones with α‐blockers offers numerous advantages over surgical alternatives. However, its effectiveness remains uncertain and with the publication of new trial data, the available evidence requires reappraisal. Objective: The aim of this study was to assess the efficacy of α‐blockers the management of ureteric lithiasis. Methods: A systematic review of the literature, with predefined search criteria, was conducted using PubMed and Embase. All randomised trials comparing α‐blocker monotherapy to placebo or standard therapy were included. Stone expulsion rate was the primary outcome measure. Secondary outcome measures were time to stone expulsion, analgesic usage and pain scores. Subgroup analyses assessed individual adrenergic antagonists and variations in standard therapy. Sensitivity analysis was based on stone location, stone size, Cochrane Risk of Bias score and study protocol. Summary effects were calculated using a random‐effect model and presented as Relative risks (RR) and mean differences (MD) for dichotomous and continuous outcome measures, respectively. Results: Sixty‐seven studies randomising 6654 patients were included in the meta‐analysis. Stone expulsion rates improved with α‐blockers (RR, 1.49; 95% CI 1.38‐1.61). Contrast enhanced funnel showed evidence of publication bias. Stone expulsion time was 3.99 days (CI −4.75 to −3.23) shorter with α‐blockers. Similarly, patients required 106.53 mg [CI −148.20 to −64.86] less diclofenac compared with control/placebo, and had 0.80 [CI −1.07 to −0.54] fewer pain episodes. Visual Analogue Scores were also reduced, −2.43 [CI −3.87 to −0.99]. All formulations of α‐antagonists all demonstrated beneficial effects over conservative treatment/placebo. Sensitivity analysis demonstrated significant effects of stone location, stone size and study design. Conclusions and Relevance: Despite the opposing results of recently published trial, current evidence continues to demonstrate a potential benefit of α‐blocker treatment particularly for distal stones over 5 mm.